WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Bayesian spatio‐temporal reconstruction reveals rapid diversification and Pleistocene range expansion in the widespread columnar cactus Pilosocereus - Pâmela Lavor; Alice Calvente; Leonardo M. Versieux; Isabel Sanmartin (Journal of Biogeography, 2019)
Aim Pilosocereus is one of the richest and most widespread genera of columnar cacti, extending from south‐west USA to southern Brazil. Most species occur in the seasonally dry tropical forest biome but can also be found in xeric microhabitats inside woody savannas (Cerrado) and moist forests (Brazilian Atlantic forest). The genus exhibits a highly disjunct distribution across the Neotropics. Using a 90% complete species‐level phylogeny, we reconstructed the spatio‐temporal evolution of Pilosocereus to explore the historical factors behind the species richness of Neotropical dry formations. Location South America, Mesoamerica, Caribbean, south‐western North America. Taxon Genus Pilosocereus (Cactaceae, Cactoideae, Cereeae). Methods We used plastid and nuclear DNA sequences and Bayesian inference to estimate phylogenetic relationships and lineage divergence times. Ancestral ranges were inferred within the Pilosocereus subgenus Pilosocereus s. s . clade using the Dispersal–Extinction–Cladogenesis model in a Bayesian framework to account for parameter estimation uncertainty and the effect of geographical distance on dispersal rates. Results Pilosocereus was recovered as polyphyletic, with representatives of other Cereeae nested within. The Pilosocereus subgenus Pilosocereus s. s . clade originated around the Pliocene–Pleistocene transition (2.7 Ma), probably within the Caatinga seasonally dry tropical forest ( SDTF ) formation. Species divergences were dated in the Middle and Upper Pleistocene, often constrained to the same geographic region but also associated to migration events to other xeric habitats in Mesoamerica and northern South America; dispersal rates were not dependent on distance. Main conclusions Diversification dynamics in the Pilosocereus subgenus Pilosocereus s. s . clade agree with other infrageneric studies in cacti. Species divergence was rapid, driven by in situ diversification and migration events between SDTF dry formations and xeric microhabitats within other biomes and probably linked to Pleistocene climatic changes. This dynamic history differs from that found in woody SDTF lineages, which are older in age and characterized by low‐dispersal rates and long‐term isolation.

Stem anatomy of Rhipsalis (Cactaceae) and its relevance for taxonomy - Alice Calvente; Regina H. P. Andreata; Ricardo C. Vieira (Plant Systematics and Evolution, 2008)

Stem anatomy of Rhipsalis (Cactaceae) and its relevance for taxonomy - Alice M. Calvente; Regina H. P. Andreata; Ricardo C. Vieira (Plant Systematics and Evolution, 2008)